A morphometric study of the midgut in resistant and non-resistant Anticarsia gemmatalis (Hubner) (Lepidoptera: Noctuidae) larvae to its nucleopolyhedrovirus (AgMNPV) - Levy, Sheila M.; Moscardi, Flavio; Falleiros, Angela M. F.; Silva, Reinaldo J. [UNESP]; Gregorio, Elisa A. [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
In this investigation, the anterior and posterior regions of the midgut of resistant (RL) and non-resistant (SL) Anticarsia gemmatalis larvae were analyzed morphometrically to characterize different regions along their length. Also, this investigation compares the results between SL and RL to improve the understanding of the resistance mechanisms to the virus. Histological sections were analyzed in a computerized system and the data were statistically analyzed by the Kruskal-Wallis test and by multivariate analysis. The midgets are morphometrically different in the two larval populations; we observed higher values in RL. The morphometric analysis of the epithelial cells showed that only columnar and goblet cells were distinct along the midgut, in both larvae, with the higher values found in the anterior region. Comparing the results between the two larval populations, all the epithelial cells presented significant differences, with RL showing the higher morphometric values. We concluded that there are regional differences along the length of midgut in SL and RL that confirm the idea of two morpho-functional distinct regions. The consistently morphometric superior values in RL indicate that this variability can be related with the resistance of A. gemmatalis to its AgMNPV. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Velvetbean caterpillar; Midgut; Morphometry; Insect resistance; Baculoviridae